Nanoparticle-Incorporated PDMS Film as an Improved Performance SPME Fiber for Analysis of Volatile Components of Eucalyptus Leaf. (12th September 2012) - Aberoomand Azar, Parviz; Mohammadiazar, Sirwan; Saber Tehrani, Mohammad; Norooz Haghi, Javad
Abstract : A new fabrication strategy was proposed to prepare polydimethylsiloxane (PDMS-) coated solid-phase microextraction (SPME) on inexpensive and unbreakable Cu fiber. PDMS was covalently bonded to the Cu substrate using self-assembled monolayer (SAM) of (3-mercaptopropyl)trimethoxysilane (3MPTS) as binder. To increase the performance of the fiber, the incorporation effect of some nanomaterials including silica nanoparticles (NPs), carbon nanotubes (CNTs), and carboxylated carbon nanotubes (CNT-COOH) to PDMS coating was compared. The surface morphology of the prepared fibers was characterized by scanning electron microscopy (SEM), and their applicability was evaluated through the extraction of some volatile organic compounds (VOCs) of Eucalyptus leaf in headspace mode, and parameters affecting the extraction efficiency including extraction temperature and extraction time were optimized. Extracted compounds were analyzed by GC-MS instrument. The results obtained indicated that prepared fibers have some advantages relative to previously prepared SPME fibers, such as higher thermal stability and improved performance of the fiber. Also, results showed that SPME is a fast, simple, quick, and sensitive technique for sampling and sample introduction of Eucalyptus VOCs.